The Scale‐up and Commercialization of Nonaqueous Na‐Ion Battery Technologies. Issue 17 (12th March 2018) - Bauer, Alexander; Song, Jie; Vail, Sean; Pan, Wei; Barker, Jerry; Lu, Yuhao
Abstract: This report provides an overview of development activities that enable the scale‐up and thereby a pathway toward the commercialization of sodium‐ion battery technologies for the energy storage market. The electrochemical performance of active materials and full cell performance of batteries developed by two startup companies, Novasis Energies, Inc. and Faradion Limited, are discussed in detail. Both companies offer low‐cost sodium‐ion battery chemistries with uniquely developed active materials that afford high rate capability and cycling stability. Their technologies are highly scalable due to the implementation of abundant and predominantly nontoxic elements and the ability to utilize common battery fabrication and manufacturing equipment. Both companies utilize active materials that are cost competitive compared to low‐cost lithium‐ion battery materials while exhibiting very similar specific capacity. In addition, improved safety characteristics with respect to operation and transportation distinguish the described sodium‐ion batteries from their incumbent lithium‐ion counterparts. The featured technology is particularly attractive for large‐scale energy storage applications. Abstract : Novasis Energies, Inc. and Faradion Limited provide an overview on the scale‐up and commercialization of nonaqueous sodium‐ion battery technologies applicable for energy storage. The cathode materials developed enable large‐scale application of sodium‐ion batteries at a lower cost compared to their lithium‐ion counterparts. Sodium‐ion batteries made by Novasis and Faradion have demonstrated superior capacity, cycling stability, and rate performance.